Bus tracking app for universities transportation - Mohammed, Siti Asma; Ariffin, Asma Hanee; Abd Aziz, Noor Azah (Psychology and Education, 2020)
Shuttle buses have become an important means of transportation for students especially for those who rely on it to go to class. However, students often face difficulty knowing the current location of the bus and its estimated arrival time. Some of them are even unaware of the bus schedule provided by higher management. Consequently, they have to wait too long for their respective buses to arrive. Hence, for the convenience of those who want to plan their journey with shuttle buses, two applications are proposed. One application will track the location of the bus and the other application will be used by the students. Both proposed applications will be used along with an Android phone since it is mostly used by students. The main objectives of developing this application are to inform users regarding the current bus location and estimated arrival time. This application also provides users real-time forum so they can start conversations with others with the same application. Besides, the driver's profile is also included for the user's future reference.